Isolation and partial characterization of Lachesis muta melanocephala coagulant proteinase: biochemical parameters of the venom - Aragón Ortiz, F. (Revista de Biología Tropical, 1988)
The coagulant proteinase of L. m. melanocephala was purified by DEAE Sephadex A-50 followed by agmatine CH- Sepharose and gel filtration on Sephadex G-100. The enzyme exhibited many of the properties adscribed to "mudasa", the coagulant proteinase from L. m. stenophirs venom. Its molecular weight by gel filtration was 35 kDa and its specific clotting activity was 702 NIH/mg of protein. A 32 fold increase in the clotting activity was obtained by purification. The coagulant proteinase exhibited esterolytic activities toward lysine and arginine esters as well as amidolytic activity. Significant differences are observed when compared with the activities of "mudasa", the former is less esterolytic and amidolytic, although its activity toward TLEME is higher. Significant differences in the activities are also observed when the venom from the Pacific and Atlantic L. muta populations (corresponding to the subspecies L. m. melanocefala and L. m. stenophyrs) are compared toward the same substrates. The Pacific type is less amidolytic and more esterolytic toward BAME and BAEE, although toward the lysine and tyrosine esters no significant differences are observed. The vemon from the Pacific population is more coagulant and less proteolytic than the venom from the Atlantic population. Analytical isoelectric focusing of both populations of venom revealed important differences in the number and intensity of the protein bands. The results here given further substantiate the taxonomical differentiation already given to the Pacific and Atlantic Costa Rican population of L. muta.